Analisis Geoteknik untuk Mengurangi Potensi Bencana Longsor di Area Tambang Nikel, Kecamatan Langgikima - Muhammad Ilham Kadar Ilham; La Ode Andimbara; Al Rubaiyn; La Ode Dzakir; Muh Karnoha Amir (Program Studi Teknik Geofisika FITK UHO, 2025)
Landslides that commonly occur in nickel mining are caused by the absence of geotechnical studies conducted by the company. Based on the importance of this issue, this study was carried out to mitigate potential landslides in the mining slope area. The objective of this research is to determine the physical and mechanical characteristics of laterite soil, recommend a stable slope design, and establish an optimal factor of safety for practical implementation. The results of this study indicate that the soil material in the limonite zone has a density of 12.65 kN/m³, cohesion of 22.55 kN/m², and an internal shear angle of 30.58˚, while the soil material in the saprolite zone has a density of 12.55 kN/m³, cohesion of 12.75 kN/m², and an internal shear angle of 28.34 ˚. The recommended overall slope design to ensure slope stability and prevent landslides includes a slope height of ≤ 45 m, a bench width of ≥ 60 m, and an overall slope angle of ≤ 37º. Additionally, the recommended factor of safety for overall slope stability is ≥ 1.1, with a landslide probability of 7.80%